If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(4 + y) + 4y = 3 (4 * 8 + y * 8) + 4y = 3 (32 + 8y) + 4y = 3 Combine like terms: 8y + 4y = 12y 32 + 12y = 3 Solving 32 + 12y = 3 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-32' to each side of the equation. 32 + -32 + 12y = 3 + -32 Combine like terms: 32 + -32 = 0 0 + 12y = 3 + -32 12y = 3 + -32 Combine like terms: 3 + -32 = -29 12y = -29 Divide each side by '12'. y = -2.416666667 Simplifying y = -2.416666667
| 78/42 | | 8(x-4)-3=6x+1 | | -6(x+2)-16=19+7 | | 7k+19=5 | | 8x-2=6x+5 | | m=6n+8 | | x+x-.66=30 | | X^2-2/3=30 | | 9x^2-5x-1= | | 91=6(12+b) | | 25-x÷2=x/3 | | 5/42x=-6/42 | | 2b-3b= | | 5/42=-6/42 | | 9x-5=7x+29 | | -5(3x-4)= | | 25c^2+20ct+4t^2=0 | | 5x+6=3x+34 | | 48v^2-120v+75=0 | | 5x+7=3x+49 | | 2x+4x+60=180 | | 100c^2-120c+36=0 | | 6x-18=-126 | | (-1/3)2 | | 5x+60+10x=180 | | 8x+3=6y-8 | | 3(y-6)-5y=-8 | | 42sqrt(4*2/41xsqrt00.125*x | | 8y/2 | | 42sqrt(4*2/41xsqrt00.125 | | 6y-2=9+10y | | 12×10^7/4×10^4 |